Obrazy kobiet i prowokatywne narracje symboliczne w twórczości malarskiej Edwarda Dwurnika - Rzońca, Apolinary (Komunizm: System - Ludzie - Dokumentacja, 2023)
The theme of a woman had been appearing throughout Edward Dwurnik’s artworks since the beginning of his career, in the early 70s, until the end of his life. This image evolved over the years. The artistdrew his inspiration from various visions of femininity, which in turn were often associated with blunt remarks about Polish reality. Dwurnik, a Polish portrait painter, depicted women in diverse symbolic configurations and at the same time referred to history and literature. He was a compulsive reader and enthusiast of them both and mentioned it on many different occasions. In the following article, the author analyses symbolism of Dwurnik’s paintings and highlights themes that might be considered taboo.